Menjaga Lingkungan Dan Budaya Dengan Tradisi Irung Irung : - - Ela Nurlaila; Maharani Putri Shafari; Mohammad Zidane; Muhammad Azmi Al-Barry; Nida Qotrunnada (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The Irung-Irung spring tradition, known as “Ngalokat Cai” or “Ruwatan Mata Air,” is an effort by the community of Cihideung Village, Parongpong District, West Bandung Regency, to preserve and maintain the increasingly scarce water sources. This tradition is carried out annually and involves various traditional rituals aimed at preserving the environment and water resources. The ceremony begins with preparations by women wearing kebaya and batik cloth, bringing flowers, rice, and coins. The ritual involves scattering flowers and prayers around the spring pool, as well as the slaughtering of a sheep as a symbol of the opening of the ruwatan. One of the important moments in this tradition is the “perang cai” (water war), where participants splash water on each other as a symbol of cleansing and purification. This tradition not only has cultural and spiritual value but also serves as a form of environmental conservation. By maintaining the cleanliness and sustainability of the spring, the community of Cihideung Village strives to preserve the vital water resources for their lives. However, the development of tourist areas around the Irung-Irung spring has reduced the space and festivity of this ceremony, although the spirit of preservation remains strong.